USE OF VIBRATION PLATFORM IN VARIOUS MEDICAL CONDITIONS (Fiep Bulletin - online, 2011)
The vibrating platform transmits mechanical vibrations to the whole body, resulting in activation of the neuromuscular spindle. The muscles contract and relax involuntarily from 30 to 50 times per second in response to a vibration that is adjustable in frequency, duration and amplitude, causing the muscles to be activated almost 100%. This leads to muscle strength, improves blood flow, it prevents and bone turnover, among others. The device can be used by sportsmen weekend, the elderly, obese, athletes, people with Alzheimer's, Parkinson's, multiple sclerosis and other diseases, except in people with cardiac pacemakers. This research comes to reports of cases of laboratory "Qualivida" in relation to an individual with Parkinson's disease, one with diabetes, two with osteogenesis imperfecta and two patients with spinal cord injury. Initially, before the work platform is the examination of bone densitometry in all individuals. In individuals with Parkinson's disease was the examination of grip strength before the beginning of exercises on the vibrating platform. After two and half weeks was applied a second test in parkinsonian dynamometry. The survey blamed increasing strength and lumbar flexion of the leg when compared with the initial examination. We also observed increased balance according to test of putting one foot in front of another. In individuals with diabetes mellitus decreased the rate of glucose in the blood. The vibrating platform is well tolerated in osteogenesis imperfecta and wheelchair showed no decubitus ulcer during the training time.
Keywords: vibrating platform; decubitus ulcer; osteogenesis imperfecta